Evolutionary Algorithms for Robust Density-Based Data Clustering. (17th January 2013) - Banerjee, Amit
Abstract : Density-based clustering methods are known to be robust against outliers in data; however, they are sensitive to user-specified parameters, the selection of which is not trivial. Moreover, relational data clustering is an area that has received considerably less attention than object data clustering. In this paper, two approaches to robust density-based clustering for relational data using evolutionary computation are investigated.